Value-at-Risk in IT Services Contracts - KAUFFMAN, Robert J. (Institutional Knowledge at Singapore Management University, 2007)
As information systems (IS) and technology solutions become increasingly service-driven, managers are faced with the task of choosing parameters such as service-levels, pricing, and contract duration. Information technology (IT) services vendors manage portfolios of contracts in which parameters, decided at inception, are often subject to future risks. The contract profit maximization decision may adversely affect the risk position of the firm's portfolio of services contracts. We propose a model to inform vendors on setting optimal parameters for IS contracts subject to acceptable levels of risk. The analytic model presented draws from IS economics research and the principles of value-at-risk (VaR) from financial economics. We provide examples which illustrate the trade-offs of profit maximizing contractual decisions to portfolio profit-at-risk (PaR). The contribution of this research is the application of VaR analysis to IS contractual decisions and the conceptualization of an economic model of IS service contracts which embeds value-at-risk constraints